Comprehensive analysis of PTPN family expression and prognosis in acute myeloid leukemia - Liu, Yong; Zhang, Jing; Du, Zefan; Huang, Junbin; Cheng, Yucai; Yi, Wenfang; Li, Tianwen; Yang, Jing; Chen, Chun (Frontiers in Genetics, 2023)
Background: Tyrosyl phosphorylation is carried out by a group of enzymes known as non-receptor protein tyrosine phosphatases (PTPNs). In the current investigation, it is hoped to shed light on the relationships between the expression patterns of PTPN family members and the prognosis of acute myeloid leukemia (AML). Methods: PTPN expression was examined using GEPIA and GEO databases. To investigate the connection between PTPN expression and survival in AML patients, we downloaded data from the Broad TCGA Firehose and Clinical Proteomic Tumor Analysis (CPTAC) of the Cancer Genome Atlas (TCGA). We used quantitative real-time PCR (qRT-PCR) to confirm that essential genes were performed in clinical samples and cell lines. We then used western blot to verify that the genes expressed in the above databases were positive in normal tissues, AML patient samples, and AML cell lines. Next, we investigated associations between genome-wide expression profiles and PTPN6 expression using the GEO datasets. We investigated the interactive exploration of multidimensional cancer genomics using the cBioPortal datasets. Using the DAVID database, a study of gene ontology enrichment was performed. The protein-protein interaction (PPI) network was created using STRING portal, and the gene-gene interaction network was performed out using GeneMANIA. Results: Data from GEO and GEPIA revealed that most PTPN family members were linked to AML. Patients with leukemia have elevated levels of several PTPN members. All of the AML patients' poor overall survival (OS, P < 0.05) was significantly linked with higher expression of PTPN1, PTPN6, and PTPN7. Additionally, clinical samples showed that the expression of PTPN 6, PTPN 7, PTPN 13, and PTPN 14 was higher than normal in AML patients (p=0.0116, p=0.0034, p=0.0092, and p=0.0057, respectively) and AML cell lines (p=0.0004, p=0.0035, p=0.0357, and p=0.0177, respectively). Western blotting results showed that the expression of PTPN6 in AML samples and AML cell lines was significantly higher than that in normal control samples. Conclusions: Differentially expressed PTPN family members were found in AML. The prognosis of patients and PTPN gene expression were shown to be correlated. PTPN6 is one of these members and may be used as an AML diagnostic and prognostic marker.